Study on Varied Bagasse Fiber and Epoxy Resin Compositions with Rice Bran Filler to Biocomposite Characteristics - Budiyati, Eni; Saputri, Fauzia Zeinandi; Prasasti, Radeva Intan Kurnia; Elwin, Muhammad Rishad (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Natural fibers, with environmental, economic, and cost advantages, are highly sought-after for biocomposite materials. In the present study, the biocomposite samples of epoxy resin (as a matrix), bagasse fiber (as reinforcement), and rice bran (as a filler) were prepared. Tensile strength, strain, and Young's modulus will be the parameters concerning which the quality of the biocomposite can be tested. On the one hand, bagasse fiber is to be a strength enhancer in the resulting biocomposite. On the other hand, rice bran may increase the biocomposite's density. The process research comprises fiber yarn from milled bagasse, alkalized fiber with KMnO4, specimen printing process, and analysis. All the fibers were treated by soaking them in 3 grams of KMnO4 solution for 30 and 45 minutes. The fiber is drained in an oven at 50 °C for ±1.5 hours. The printed fiber onto a specimen mold was printed with a mixture of epoxy resin and rice bran (1:1 w/w) and left for one day. Variation in the fiber mass was at 3, 4, and 5 grams. The sizes of the specimens were similar to the size of the mold according to ASTM D-638 type IV. Then, the fibers were removed from the mold and tested for tensile strength, strain, and Young's modulus. The results show that the greater the fiber mass, the greater the tensile strength value. These findings indicate that the tensile strength was optimized after soaking for 45 minutes with 5-gram fiber weight, which resulted in the tensile strength of 26.32±0.25 MPa, strain of 9.65±0.14%, Young's Modulus of 3.29±0.05 MPa, and water absorption of 41.99%.